PENGARUH DUKUNGAN SOSIAL TERHADAP KECEMASAN BELAJAR PASCA PANDEMI COVID-19 PADA SISWA SMA LABORATORIUM UPGRIS SEMARANG - Harmanda, Pradana Wahyu Rizky; Ismanto, Heri Saptadi; Lestari, Farikha Wahyu (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2024)
The Covid-19 pandemic has also brought society towards a new system. Many aspects are affected by the COVID-19 control policy, one of which is the learning aspect. Researchers also conducted a preliminary study to understand the phenomenon of learning anxiety in Upgris Laboratory High School students through interviews with 3 teachers. Based on the interview results, it can be concluded that learning anxiety during online learning shows sufficient symptoms to be identified. Furthermore, learning anxiety after the pandemic is considered to have decreased because teachers can play a more active role in guiding students. Based on the research results that have been described, it can be concluded that social support has a negative effect on learning anxiety. This means that the higher the level of social support received by students post-pandemic, the lower their level of learning anxiety.